2020
DOI: 10.1101/2020.12.22.423950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sting orchestrates the crosstalk between polyunsaturated fatty acids metabolism and inflammatory responses

Abstract: SummaryInflammatory disorders are major health issues in which immune function and metabolic homeostasis are concertedly altered. Yet, the molecular mechanisms coordinating innate and metabolic pathways in homeostatic conditions are poorly understood. Here, we unveil a negative regulatory feedback loop involving the Stimulator of interferon genes (Sting) and the Fatty acid desaturase 2 (Fads2). At steady state, Sting regulates FA metabolism by repressing the activity of the Fads2 enzyme responsible for the des… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Thus, besides preventing cell death, additional mechanism by the AQ allele, e.g. fatty acid metabolism 37,69 , is involved in curing SAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, besides preventing cell death, additional mechanism by the AQ allele, e.g. fatty acid metabolism 37,69 , is involved in curing SAVI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to metabolic and antioxidant dimensions, ferroptosis regulation is also influenced by immunerelated signaling cascades. Specifically, the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) [21] , JAK-STAT1 [22][23] , TGF-β1-Smad3 signaling pathways have been implicated in the delicate orchestration of ferroptosis [24] . This interplay underscores the complex interplay among metabolism, redox biology, and immunity in shaping the fate of cells undergoing ferroptosis.…”
Section: Ferroptosis-related Signalsmentioning
confidence: 99%
“…The main substrate of lipid peroxidation, PUFAs, are also closely associated with cGAS-STING signaling transduction. Through molecular docking analysis and in vitro experiments, Vila et al demonstrated that PUFAs specifically bond to the cGAMP-binding domain of STING, thereby blocking downstream TBK1 and IRF3 phosphorylation and inhibiting STING-mediated inflammatory response [21] . Additionally, STING may impede the formation of PUFAs by inhibiting the fatty acid desaturase 2-associated desaturation activity [21] , thereby hindering the occurrence of ferroptosis [64] .…”
Section: Sting-mfn1/2 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…First, multiple post-translational modifications influence signaling output (42)(43)(44). Second, STING can be directly activated by bacterial cyclic di-nucleotides (45,46), while its activation is skewed by alternative di-nucleotides (16) or other metabolites (47). Third, co-sensors, co-factors and alternative upstream STING activators have been described, that can operate in cell type-specific manners (23,(48)(49)(50).…”
Section: Cytosolic Nucleic Acid Detection: Sting As a Central Signaling Hubmentioning
confidence: 99%